Perbandingan Kadar Hesperidin pada Beberapa Kulit Jeruk Menggunakan Spektrofotometer UV-Vis - Farhan Rassya Fadhilah; Vivi Anggia; Priyanti Priyanti; Hendri Aldrat (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2025)
Orange peel is a high-potential agro-waste and a rich natural source of hesperidin, a flavonoid compound with multiple health benefits, yet comparative data on hesperidin level across different citrus varieties are still limited. This study aimed to compare the yield and content of hesperidin among different citrus peels and to evaluate the reliability of UV-Vis spectroscopy for its quantification determination. Peels from Medan orange (C. sinensis), baby Java (C. sinensis), key lime (Citrus aurantiifolia), jeruk limo (C. amblicarpa), and kaffir lime (C. hystrix). Samples were extracted through a tiered Soxhletation process with n-hexane and methanol solvents, followed by acidification and crystallization to obtain hesperidin. Characterization was carried out using melting point analysis and thin-layer chromatography, while hesperidin content was determined with a UV-Vis spectrophotometer at a maximum wavelength of 283 nm. The results showed that citrus species significantly affected hesperidin yield and content, with with baby Java orange peel producing the highest amount (5.72%), followed by Medan orange (3.98%), lime (0.46%), jeruk limo (0.37%), and kaffir lime (0.16%). The UV-Vis spectrophotometry method proved reliable, showing linearity (r² = 0.998), accuracy (82.00%), and precision (%RSD = 0.964%). Content analysis confirmed that baby Java orange peel isolate had the highest hesperidin concentration (11.59 ppm, purity 86.14%) among other orange peel isolates compared to standard pure hesperidin. These findings highlight the variability of hesperidin content among citrus species and emphasize the importance of raw material selection for pharmaceutical and nutraceutical application.